PHYSICAL EDUCATION OF STUDENT YOUTH IN MODERN CONDITIONS - Shakhnoza , Kholova; Ulfatoy, Khayitova; Orif, Sobirov (International Journal of Psychosocial Rehabilitation, 2020)
Today a considerable number of researches is devoted to students’ physical education and healthy lifestyle of today’s youth. Most authors agree that there is a necessity for structural changes in the process of students’ physical education in order to improve their health and develop their physicality. The article deals with the various structural forms of organization of students’ physical education